Why do we Need to Know the Electrical Resistivity Structure of Oceanic Lithosphere?. Issue 1 (1st December 2018) - Macfarlane, Jake; Heinson, Graham
Abstract : Regional-scale continental magnetotelluric (MT) programs such as AusLAMP are naturally bounded by the continental shelf and electrically-conducting seawater. Within a few hundred kilometres of the coastline, long-period MT data may be strongly influenced by induction in the seawater, a phenomenon known as the coast-effect. Thus, 3D inversion of gridded long-period MT data for continental lithosphere models requires good constraints on the resistivity of the seawater, oceanic crust and upper mantle, and into the asthenosphere. In this paper, we discuss the concept of a horizontal adjustment distance. This is the horizontal distance away from a major contrast in electrical conductance at which the anomalous electric fields are attenuated by a factor of 1/e from a 1D response, and is somewhat analogous to the more widely-known skin-depth concept. For seafloor MT, this adjustment distance can be thousands of kilometres. Inland, the effect depends on the conductance of the sedimentary cover, and the depth-integrated resistivity of the upper crust, and can vary from a few kilometres to hundreds of kilometres. We discuss the implications in terms of 3D smooth inversion that inherently minimises gradients in subsurface resistivity and suggest that the coast effect may be significantly underestimated in some continental models.